2022
DOI: 10.3389/fphys.2022.1005404
|View full text |Cite
|
Sign up to set email alerts
|

GERD-related chronic cough: Possible mechanism, diagnosis and treatment

Abstract: GERD, or gastroesophageal reflux disease, is a prevalent medical condition that affects millions of individuals throughout the world. Chronic cough is often caused by GERD, and chronic cough caused by GER is defined as GERD-related chronic cough (GERC). It is still unclear what the underlying molecular mechanism behind GERC is. Reflux theory, reflex theory, airway allergies, and the novel mechanism of esophageal motility disorders are all assumed to be linked to GERC. Multichannel intraluminal impedance combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 178 publications
(191 reference statements)
0
6
0
4
Order By: Relevance
“…In the context of exploring the causal relationship between GERD and extraesophageal manifestations such as chronic cough, two principal mechanistic frameworks have been highlighted: the reflex theory and the reflux theory 47 , 48 . The reflux theory hypothesizes that the refluxate may ascend to the upper airways during reflux occurrences, inducing respiratory manifestations through micro-aspiration and direct stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of exploring the causal relationship between GERD and extraesophageal manifestations such as chronic cough, two principal mechanistic frameworks have been highlighted: the reflex theory and the reflux theory 47 , 48 . The reflux theory hypothesizes that the refluxate may ascend to the upper airways during reflux occurrences, inducing respiratory manifestations through micro-aspiration and direct stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] Pathological reflux directly irritates the mucous membrane of the throat and damages esophageal nerve endings leading to throat diseases, [ 48 ] while acidification of the esophagus increases sensitivity to coughing. [ 49 ] The mechanism of chest pain caused by gastroesophageal reflux is unclear. Considering that both the heart and digestive organs are innervated by vegetative nerves, the nerve conduction processes of both may converge in neurons in the same spinal cord segment and share conduction pathways, thus, the central system may misinterprets pain information from visceral afferents as coming from superficial body tissues and manifests as chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the tickle in the throat may be a special presentation of acid reflux or laryngopharyngeal reflux. In addition to the reflux mechanism, a vagally mediated reflex process in distal esophageal reflux could also cause extraesophageal symptoms (24). The reflex mechanism could explain why most reflux events occurred in the distal esophagus in patients with chronic cough (80%) (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…It requires multiple investigations, such as spirometry, bronchial challenge, induced sputum test for differential cells, and 24-hour esophageal pH value monitoring. These investigations, especially 24-hour esophageal pH value monitoring are time-consuming, expensive, and unavailable in the primary care setting. Our previous study found that a few clinical features could indicate a single common cause of chronic cough, such as nocturnal cough for CVA, postnasal dripping and history of sinusitis for UACS, heartburn, belching, acid regurgitation and cough after meals for GERC (6).…”
Section: Introductionmentioning
confidence: 99%